2018
DOI: 10.18535/jmscr/v6i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of ovarian lesions in tertiary care institute of central India

Abstract: JMSCR Vol||06||Issue||01||Page 32575-32581||January 2018Introduction The ovarian pathology is currently among the widest and most complex problems in modern gynecology mainly through ovarian tumours. Despite its small size, ovary requires attention of several specialties like endocrinology, gynecology and pathology. It is an organ with a complex physiology, which is always changing, undergoing more structural changes than any other organ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…The most common neoplastic lesion was benign serous cystadenoma. This is comparable with studies done by Panchonia et al [13] and Serous carcinoma was the most common malignant lesion in our study, consistent with studies done by Modi et al [15] Mature cystic teratomas were common among the germ cell tumors in the present study followed by immature teratoma. Incidence is similar to studies conducted by Gupta SC et al [17] and Couto F et al…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most common neoplastic lesion was benign serous cystadenoma. This is comparable with studies done by Panchonia et al [13] and Serous carcinoma was the most common malignant lesion in our study, consistent with studies done by Modi et al [15] Mature cystic teratomas were common among the germ cell tumors in the present study followed by immature teratoma. Incidence is similar to studies conducted by Gupta SC et al [17] and Couto F et al…”
Section: Discussionsupporting
confidence: 94%
“…In our study among the neoplastic lesions 60% were benign, 36.7% were malignant and 3.3% were borderline tumors. This is comparable with studies conducted by Panchonia et al [13] , Phukan et al [14] , Pilli et al [8] and Patel et al [9] All the studies showed that majority of the neoplastic lesions were benign followed by malignant and borderline tumors. Surface epithelial tumour was the most common neoplastic lesion according to WHO classification of tumors of ovary [4] .…”
Section: Discussionsupporting
confidence: 90%